A High-Accuracy and Conservative Unstructured Overset Grid data transfer Method for Numerical Simulation of Turbomachinery. Issue 1 (February 2021) - Cui, P C; Tang, J; Li, B; Li, H; Wu, X J; Ma, M S
Abstract: The overset grid method is getting more and more popular in the numerical simulation of turbomachinery, especially in the simulation of wind turbines. Reasonable interpolation between overset grid interfaces is one of the bases to ensure correct calculation of flow fields, non-conservative interpolation is insufficient to guarantee the mass fluxes in the numerical simulation of turbomachinery. This paper develops a conservative interpolation method for hybrid overset mesh based on supermesh technology and centre-based finite volume method. A method to build the local supermesh during overset grid interface by the cell-cut algorithm is presented, and flow field variables could be interpolated conservatively during overset meshes with second-order accuracy via the local supermesh. Numerical results show that the proposed method is strictly conservative for second-order distributed flow variables. Compared with trilinear interpolation method and reverse distance-weighted interpolation method, the method in this paper decreases the numerical errors and the variables are interpolated more accurately. Engineering cases show that the method in this paper is robust and practical for engineering applications.